Geeks, girls, and secret identities - Jung, Mike (Arthur A. Levine Books, 2012)
Twelve-year-old Vincent and his fellow members of the Captain Stupendous Fan Club help out when someone new becomes Earth's most famous superhero, without knowing anything about him, just as evil Professor Mayhem and his robot arrive in Copperplate City.